2012
DOI: 10.1111/j.1464-410x.2011.10822.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sympathetic neuroeffector transmission in human corpus cavernosum

Abstract: Study Type – Aetiology (case control) Level of Evidence 2b What's known on the subject? and What does the study add? In the present study the mechanisms regulating EFS‐evoked neurogenic contraction in the human corpus cavernosum (HCC) were investigated. Overall, our data adds to current knowledge that the NO‐independent heme dependent activation of sGC and the RhoA/Rho‐kinase signaling pathways play an important role in the regulation of neurogenic contractile activity in HCC tissue. OBJECTIVE To investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In an attempt to study, the contractile response elicited only by the adrenergic nerve component of EFS, the tissues were treated with a non‐selective NO synthase inhibitor, L‐N(G)‐nitroarginine methyl ester (L‐NAME, 100 µM), and the muscarinic receptor antagonist atropine (1 µM) for 30 min to eliminate nitrergic and cholinergic influences . The increases in the tension of the muscle in contractile response to EFS and Phe were measured in gram/gram tissue …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to study, the contractile response elicited only by the adrenergic nerve component of EFS, the tissues were treated with a non‐selective NO synthase inhibitor, L‐N(G)‐nitroarginine methyl ester (L‐NAME, 100 µM), and the muscarinic receptor antagonist atropine (1 µM) for 30 min to eliminate nitrergic and cholinergic influences . The increases in the tension of the muscle in contractile response to EFS and Phe were measured in gram/gram tissue …”
Section: Methodsmentioning
confidence: 99%
“…14 The increases in the tension of the muscle in contractile response to EFS and Phe were measured in gram/ gram tissue. 15…”
Section: Isometric Tension Measurementsmentioning
confidence: 99%
“…It is worthwhile mentioning that even the alphaadrenergic blockers, one of the main drugs to treat LUTS/BPH, facilitate relaxation of isolated fibers of smooth cavernous muscles [Gur et al 2008[Gur et al , 2012; in addition these agents can revert functional and molecular alterations triggered by partial vesical obstruction [Gur et al 2008].…”
Section: Discussionmentioning
confidence: 99%
“…The authors verified that functional (diminished contractions in cavernous body muscle fibers, induced by acetylcholine and electrical stimulus) and molecular changes (alteration in expression and bioavailability of nitric oxide) were partially reverted by treating with an alpha-adrenergic blocker. More recently, the same group [Gur et al 2012] demonstrated alpha-adrenergic blockage produces relaxation of the muscle fibers of human cavernous body that is comparable to PDE-5i. Furthermore, in the past it was shown that the intracavernous and oral use of phentolamine and phenoxybenzamine caused erection in men with erectile dysfunction [Padma-Nathan et al 2002;Glina et al 2008].…”
Section: Use Of the Same Medications To Simultaneously Treat Ed And Lmentioning
confidence: 99%
“…Penile flaccidity process primarily have been stimulated by the sympathetic nervous system, where the release of norepinephrine (NA) by adrenergic neurons stimulates its α 1 and α 2 receptors in the smooth muscle of the penile vessels and corpus cavernosum, inducing its contraction and reduction of the blood flow ( Goldstein, 2000 ; Gur et al., 2012 ; Traish et al., 2015 ).…”
Section: Physiological Mechanisms Of Flaccidity and Penile Erectionmentioning
confidence: 99%